Adolescent self-report and parent proxy-report of health-related quality of life: an analysis of validity and reliability of PedsQLTM 4.0 among a sample of Malaysian adolescents and their parents - V. Sanker, Kaartina; Chin, Yit Siew; Rezali, Fara Wahida; Woon, Fui Chee; Hiew, Chu Chien; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir (BioMedical Central, 2015)
Background The Pediatric Quality of Life Inventory™ Generic Core Scales (PedsQL™) 4.0 is a generalized assessment of health-related quality of life (HRQoL) based on adolescent self-report and parent proxy-report. This study aims to determine the construct validity and reliability of PedsQL™ 4.0 among a sample of Malaysian adolescents and parents. Methods A cross-sectional study was carried out at three selected public schools in the state of Selangor. A total of 379 Malaysian adolescents completed the PedsQL™ 4.0 adolescent self-report and 218 (55.9%) parents completed the PedsQL™ 4.0 parent proxy-report. Weight and height of adolescents were measured and BMI-for-age by sex was used to determine their body weight status. Results There were 50.8% male and 49.2% female adolescents who participated in this study (14.25 ± 1.23 years). The prevalence of overweight and obesity (25.8%) was four times higher than the prevalence of severe thinness and thinness (6.1%). Construct validity was analyzed using Confirmatory Factor Analysis (CFA). Based on CFA, adolescent self-report and parent proxy-report met the criteria of convergent validity (factor loading > 0.5, Average Variance Extracted (AVE) > 0.5, Construct Reliability > 0.7) and showed good fit to the data. The adolescent self-report and parent proxy-report exhibited discriminant validity as the AVE values were larger than the R2 values. Cronbach’s alpha coefficients of the adolescent self-report (α = 0.862) and parent proxy-report (α = 0.922) showed these instruments are reliable. Parents perceived the HRQoL of adolescents was poorer compared to the perception of the adolescent themselves (t = 5.92, p < 0.01). There was no significant difference in total HRQoL score between male and female adolescents (t = 0.858, p > 0.05). Parent proxy-report was negatively associated with the adolescents’ BMI-for-age (r = -0.152, p < 0.05) whereas no significant association was found between adolescent self-report and BMI-for-age (r = 0.001, p > 0.05). Conclusion Adolescent self-report and parent proxy-report of the PedsQL™ 4.0 are valid and reliable to assess HRQoL of Malaysian adolescents. Future studies are recommended to use both adolescent self-report and parent-proxy report of HRQoL as adolescents and parents can provide different perspectives on HRQoL of adolescents.